Construção e formalização do saber em montagem estrutural de aeronaves - Souza, Túlio Oliveira de (2008)
The aim of this study was to understand the technique construction role as well as the knowledge in consolidation of the aeronautics design and upbringing productive competence. In this way, it identified the representations from different actors over the constraints that acted in the start of the aeronautics production, and turned evident in the strategies adopted by assemblers, and managers facing the constraints. It was done an ergonomic analysis of this work, based on observations, interviews, surveys and confrontation group. The riveter assembler, while realize his work activity provoke a sense motor action and promotes a confrontation of intentions, gesture and results producing news ways of know-how . The new know-how , therefore, seem to comply an absortion cycle by the productive organization which is shaped by the product maturity process. The viability of manufacturability makes itself up to the subject ability to incorporate adjustments or indicates changes. The system stability and aircraft own homologation derives from the technique formation, the meta-functional activity and the incorporation of the assemblers knowledge.